Relationships among speed of processing, aptitude, and working memory in elementary students - McEachern, Alissa Kendall, author; Gloeckner, Gene, advisor; Coke, Pam, committee member; Frederiksen, Heidi, committee member; Kohen, Karen, committee member (Colorado State University. Libraries, 2017)
This research explores the relationships between speed of processing, verbal and quantitative aptitude, and working memory for elementary age students. Students with impaired processing speed often struggle in elementary school and can be incorrectly identified as lazy or unintelligent. This can have lasting consequences on their self-esteem and future academic success. The findings of this research suggest that the combination of processing speed, working memory and academic achievement in reading does not adequately predict verbal intelligence. However, the model indicates that there is a relationship between the variables of processing speed, working memory, and mathematic achievement to predict quantitative intelligence. Additionally, there was no statistically significant correlation of processing speed and verbal aptitude for this sample. Likewise, there was no statistically significant correlation of speed of processing and quantitative aptitude. The research shows a statistically significant difference between processing speed and academic achievement in reading and in mathematics; reading and speed of processing, as well as mathematics and speed of processing. Ultimately, this research suggests that students with impaired processing speed do not demonstrate impaired aptitude in reading or mathematics. However, this research also suggests they may struggle with academic achievement in both reading and mathematics. This gap between aptitude and achievement is an important characteristic to remediate so that students with lower processing speeds can be successful in school.
Keywords: aptitude; CToPP; working memory; CogAT; achievement; processing speed